Rapid construction of tricyclic tetrahydrocyclopenta[4,5]pyrrolo[2,3-b]pyridine via isocyanide-based multicomponent reaction - Chen, Xiu-Yu; Han, Ying; Sun, Jing; Yan, Chao-Guo (Beilstein Journal of Organic Chemistry, 2024)
An efficient protocol for the synthesis of polyfunctionalized tetrahydrocyclopenta[4,5]pyrrolo[2,3-b]pyridine-3,4b,5,6,7(1H)-pentacarboxylates was developed by a three-component reaction. In the absence of any catalyst, the three-component reaction of alkyl isocyanides, dialkyl but-2-ynedioates and 5,6-unsubstituted 1,4-dihydropyridines in refluxing acetonitrile afforded polyfunctionalized tetrahydrocyclopenta[4,5]pyrrolo[2,3-b]pyridine-3,4b,5,6,7(1H)-pentacarboxylates in high yields and with high diastereoselectivity. The reaction was finished by in situ generation of activated 5-(alkylimino)cyclopenta-1,3-dienes from addition of alkyl isocyanide to two molecules of but-2-ynedioates and sequential formal [3 + 2] cycloaddition reaction with 5,6-unsubstituted 1,4-dihydropyridine.
Keywords: [3 + 2] cycloaddition; cyclopenta-1,3-diene; cyclopenta[4,5]pyrrolo[2,3-b]pyridine; 1,4-dihydropyridine; electron-deficient alkyne; isocyanide